Oxygen vacancies engineering in electrocatalysts nitrogen reduction reaction - Zhu, Haijiang; Wang, Chao; He, Yuling; Pu, Yi; Li, Peiwen; He, Liang; Huang, Xianglan; Tang, Wu; Tang, Hui (Frontiers in Chemistry, 2022)
Ammonia is important, both as a fertilizer and as a carrier of clean energy, mainly produced by the Haber-Bosch process, which consumes hydrogen and emits large amounts of carbon dioxide. The ENRR (Electronchemical Nitrogen Reduction Reaction) is considered a promising method for nitrogen fixation owing to their low energy consumption, green and mild. However, the ammonia yield and Faraday efficiency of the ENRR catalysts are low due to the competitive reaction between HER and NRR, the weak adsorption of N2 andthe strong N≡N triple bond. Oxygen vacancy engineering is the most important method to improve NRR performance, not only for fast electron transport but also for effective breaking of the N≡N bond by capturing metastable electrons in the antibonding orbitals of nitrogen molecules. In this review, the recent progress of OVs (oxygen vacancies) in ENRR has been summarized. First, the mechanism of NRR is briefly introduced, and then the generation methods of OVs and their applicationin NRR are discussed, including vacuum annealing, hydrothermal method, hydrogen reduction, wet chemical reduction, plasma treatment and heterogeneous ion doping. Finally, the development and challenges of OVs in the field of electrochemical nitrogen fixation are presented. This review shows the important areas of development of catalysts to achieve industrially viable NRR.